(untitled) (Research, Society and Development, 2021)
Society is marked by constructs woven throughout history and which are instilled in the social imagination of subjects as legitimizers of an established order and when debates are proposed in an itinerary contrary to the normative, these are considered controversial themes. The inclusion of gender identity and sexual orientation as an agenda to be discussed brings with it this concern, as it unwittingly interferes with thought structures built under the aegis of an indisputable pattern of sexual behavior and gender expression, especially when the locus of discussion occurs at school. In this sense, this work has as its theme to panoramically analyze published writings and legislation that can support the debate about gender identity and sexual orientation, mainly within the school space. We sought to carry out a bibliographical survey from sources and legislation concerning the area, without intending to trace any ideological imposition that presupposes an exhaustion of the subject when it collides with hegemonic patterns of thought. It was proposed, then, a qualitative research, aiming to remove from invisibility themes like this that carry the central theme of this work. Thus, it could be verified that entering this discussion in society and in school is urgent and necessary and this can only be done with the opening to qualified debate, in an attempt to remove diversity from invisibility and destroy barriers built by the perpetuation of social concepts that were made over time and were appropriated as being immutable truths within a standard logic socially validated over the centuries.